STK25 Regulates Cardiovascular Disease Progression in a Mouse Model of Hypercholesterolemia. Issue 8 (August 2018) - Cansby, Emmelie; Magnusson, Elin; Nuñez-Durán, Esther; Amrutkar, Manoj; Pedrelli, Matteo; Parini, Paolo; Hoffmann, Jenny; Ståhlman, Marcus; Howell, Brian W.; Marschall, Hanns-Ulrich; Borén, Jan; Mahlapuu, Margit
Abstract : Objective—: Recent cohort studies have shown that nonalcoholic fatty liver disease (NAFLD), and especially nonalcoholic steatohepatitis (NASH), associate with atherosclerosis and cardiovascular disease, independently of conventional cardiometabolic risk factors. However, the mechanisms underlying the pathophysiological link between NAFLD/NASH and cardiovascular disease still remain unclear. Our previous studies have identified STK25 (serine/threonine protein kinase 25) as a critical determinant in ectopic lipid storage, meta-inflammation, and progression of NAFLD/NASH. The aim of this study was to assess whether STK25 is also one of the mediators in the complex molecular network controlling the cardiovascular disease risk. Approach and Results—: Atherosclerosis was induced in Stk25 knockout and transgenic mice, and their wild-type littermates, by gene transfer of gain-of-function mutant of PCSK9 (proprotein convertase subtilisin/kexin type 9), which induces the downregulation of hepatic LDLR (low-density lipoprotein receptor), combined with an atherogenic western-type diet. We found that Stk25 −/− mice displayed reduced atherosclerosis lesion area as well as decreased lipid accumulation, macrophage infiltration, collagen formation, and oxidative stress in aortic lesions compared with wild-type littermates, independently from alterations in dyslipidemia. Reciprocally, Stk25 transgenic mice presented aggravated plaque formation and maturation compared with wild-type littermates despite similar levels of fasting plasma cholesterol. We also found that STK25 protein was expressed in all layers of the aorta, suggesting a possible direct role in cardiovascular disease. Conclusions—: This study provides the first evidence that STK25 plays a critical role in regulation of cardiovascular disease risk and suggests that pharmacological inhibition of STK25 function may provide new possibilities for prevention/treatment of atherosclerosis. Abstract : Supplemental Digital Content is available in the text.